Low maternal serum concentrations of mannose‐binding lectin are associated with the risk of shorter duration of pregnancy and lower birthweight. (25th June 2018) - Koucký, M.; Malíčková, K.; Kopřivová, H.; Cindrová‐Davies, T.; Hrbáčková, H.; Černý, A.; Šimják, P.; Pařízek, A.; Zima, T.
Abstract: Chronic inflammation has been implicated as the underlying mechanism responsible for the pathophysiology of preterm labour. Mannose‐binding lectin (MBL) plays a central role in the innate immune response and is thus an important component of the first line of defense. The aim of this study was to investigate whether serum concentrations of MBL correlated with the incidence of preterm birth and low birthweight in a cohort of women with signs of threatened preterm birth. A cohort of 60 patients who presented with regular contractions and/or short cervix (group A) between 24 and 32 weeks of gestation and 20 healthy controls (group B) who had no pregnancy complications and delivered at term were recruited into a prospective study. The following outcomes were recorded: presence of preterm labour and birthweight in all patients. MBL and high sensitivity C‐reactive protein levels were measured in all serum samples. The serum concentrations of MBL were significantly reduced in patients with threatened preterm labour (Group A), compared to the control Group B. Furthermore, infants born to Group A mothers with MBL deficiency (n = 13, MBL ≤100 ng/mL) had significantly lower birthweights, compared to those born to Group A women with normal MBL serum concentrations ( P < .0001). Our small cohort study demonstrated a strong association between MBL deficiency and preterm delivery, and associated low birthweight. MBL deficiency could thus be considered an important risk factor for preterm birth.